2020
DOI: 10.1159/000510126
|View full text |Cite
|
Sign up to set email alerts
|

Selective Polymyxin Hemoperfusion in Complex Therapy of Sepsis in Children after Cardiac Surgery

Abstract: <b><i>Background:</i></b> To date, sepsis remains one of the main challenges of intensive care in pediatrics. Newborns with low birth weight and infants with chronic diseases and congenital disorders are particularly at risk. The incidence of infectious complications in pediatric cardiac surgery is known to be approximately 15–30%. The main etiological factor of sepsis is endotoxin. <b><i>Aim:</i></b> To evaluate the efficiency and safety of polymyxin (PMX) B-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Other authors have already studied blood purification therapies in pediatric septic shock; Kawai et al ( 31 ) used therapeutic plasma exchange (TPE) in children with multiple organ dysfunction syndrome (MODS) due to sepsis and requiring ECMO, showing an improved VIS and organ failure index after a median of three TPE cycles. Polymyxin-B hemoadsorption with PMX-05 cartridges was applied in 15 children with septic shock; the authors reported a trend towards an improvement in hemodynamics after two sessions of therapy, although inotropic agent requirements did not change over time ( 32 ). More recently, Saetang et al described the use of PMX-20R (a modified polymyxin-B cartridge circuit for pediatric use) in 6 children and reported a significant reduction in PELOD-2 and VIS scores after two sessions of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have already studied blood purification therapies in pediatric septic shock; Kawai et al ( 31 ) used therapeutic plasma exchange (TPE) in children with multiple organ dysfunction syndrome (MODS) due to sepsis and requiring ECMO, showing an improved VIS and organ failure index after a median of three TPE cycles. Polymyxin-B hemoadsorption with PMX-05 cartridges was applied in 15 children with septic shock; the authors reported a trend towards an improvement in hemodynamics after two sessions of therapy, although inotropic agent requirements did not change over time ( 32 ). More recently, Saetang et al described the use of PMX-20R (a modified polymyxin-B cartridge circuit for pediatric use) in 6 children and reported a significant reduction in PELOD-2 and VIS scores after two sessions of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Методы экстракорпоральной гемокоррекции широко применяются в комплексной терапии критических состояний, обусловленных инфекционной патологией и сепсисом, однако, в силу недостаточного количества рандомизированных клинических исследований, до сих пор не относятся к методам терапии первого уровня доказательности, а число исследований, посвященных применению этих методов у пациентов детского возраста, в настоящее время ограничено [13,14].…”
Section: актуальностьunclassified
“…Some reports have recently described the application of hemoadsorption in the pediatric setting. Both DH-PMX [51] and CytoSorb ® have been safely used in cases series of septic shock [52], hemophagocytic lymphohistiocytosis [53], and multi-organ failure (MOF) [54], but pediatric randomized trials are not currently planned. More information on this delicate population will need to be provided by large prospective databases.…”
Section: Cytosorb ® Hemoperfusionmentioning
confidence: 99%